An ablative pulsed plasma thruster with a segmented anode. (15th December 2017) - Zhang, Zhe; Ren, Junxue; Tang, Haibin; Ling, William Yeong Liang; York, Thomas M
Abstract: An ablative pulsed plasma thruster (APPT) design with a 'segmented anode' is proposed in this paper. We aim to examine the effect that this asymmetric electrode configuration (a normal cathode and a segmented anode) has on the performance of an APPT. The magnetic field of the discharge arc, plasma density in the exit plume, impulse bit, and thrust efficiency were studied using a magnetic probe, Langmuir probe, thrust stand, and mass bit measurements, respectively. When compared with conventional symmetric parallel electrodes, the segmented anode APPT shows an improvement in the impulse bit of up to 28%. The thrust efficiency is also improved by 49% (from 5.3% to 7.9% for conventional and segmented designs, respectively). Long-exposure broadband emission images of the discharge morphology show that compared with a normal anode, a segmented anode results in clear differences in the luminous discharge morphology and better collimation of the plasma. The magnetic probe data indicate that the segmented anode APPT exhibits a higher current density in the discharge arc. Furthermore, Langmuir probe data collected from the central exit plane show that the peak electron density is 75% higher than with conventional parallel electrodes. These results are believed to be fundamental to the physical mechanisms behind the increased impulse bit of an APPT with a segmented electrode.